Pengenalan dan Karakterisasi Tumbuhan Berbasis Permainan Interaktif untuk Meningkatkan Pemahaman Siswa Tentang Keanekargaman Tumbuhan di Lingkungan Sekolah SDN 2 Merembu - Apriani, Reni; Farida Jufri, Afifah; Pranggawan Azhari, Anjar; Jihadi, Amrul; Hidayatun Nufus, Novita (Fakultas Pertanian Universitas Mataram, 2025)
Abstract: Plant diversity is an important topic in science education at the elementary school level. Unfortunately, conventional teaching methods are often perceived as less engaging for students, resulting in an incomplete understanding of plant diversity, especially in their surrounding environment. This community service activity was conducted to enhance students’ understanding of plant diversity at SDN 2 Merembu through an interactive game-based learning approach. The school’s garden and yard, which contain various types of plants, were used as direct learning media through educational games to create a fun, active, and participatory learning atmosphere. In this activity, students were introduced to different plant species around the school and involved in simple plant characterization activities based on morphological traits. Through games such as “Tebak Tumbuhan” and “Jelajah Taman Sekolah,” students were trained to observe and identify the unique characteristics of each plant species. The results showed strong student enthusiasm and participation during the game-based learning process. The warm and enthusiastic responses suggest that game-based educational strategies can be a relevant and appealing learning method for elementary school children. Keywords: Ecosystem; Plant Diversity; Educational Games; School Environment